Concordância nominal entre o artigo e o nome em português língua estrangeira - Nhatuve, Diocleciano (Linguarum Arena, 2020)
This study aims to describe the aspects of agreement between articles and nouns in noun phrases written by 2nd and 3rd year Portuguese learners at the University of Zimbabwe. The study is based on qualitative and quantitative approaches and on non-native language learning theories. In order to identify common trends of learners of Portuguese as foreign language and those that are particular to the target group, we used a control group of A2 and B1 Portuguese learners at the University of Coimbra. Results indicate that although the deviant trends are below the agreement according the European Portuguese, they are nonetheless worrying from the educational point of view. The projection of the plural and feminine in the noun-heads as well as the concentration of gender deviations involving nouns belonging to thematic class – a are particular trends of Zimbabwean learners of the Portuguese language. These tendencies can be explained based on the action of previous linguistic knowledge, the manifestation of interlanguage phases and the principles of the input processing.